ADOPTION LEVEL OF INFORMATION TECHNOLOGY IN COMPANIES WITH MILLENNIAL LEADERSHIP: THE URGENCY OF ONE ON ONE TRAINING AND INTERPERSONAL COMMUNICATION - Marelda, Rebecka; Wikaningrum, Tri (Universitas Brawijaya, Indonesia, 2022)
This study aims to determine and analyze the influence of millennial leadership style, one-on-one training, and interpersonal communication on the adoption level of infor- mation technology. This study uses quantitative methods. The population of this study is employees of PT. Apparel One Indonesia, Semarang. The sample amount in this study is 100 samples, but only 92 samples could be processed. The data analysis method used is Smart PLS 3.0 - SEM. The results show that the millennial leadership style and one-on-one training significantly and positively affect interpersonal communication. In contrast, the millennial leadership style has no significant impact on the adoption level of information technology. One-on-one training and interpersonal communication significantly and positively affect the adoption level of information technology. Interpersonal communication can mediate millennial leadership style and one-on-one training on adopting information technology. For future research, it is recommended to use other leadership styles and different training methods and add more sample quantity. The implications of this research are interpersonal communication and one-on-one training methods formed in the work environment have been going well. Therefore, communication through interaction between individuals and training methods in the form of discussion should be maintained and improved.